Panasonic: security camera for home use / Nurulhafizah Shukhri - Shukhri, Nurulhafizah (2022)
Nowadays, many technologies have been developed to make continually advancements either for gadget or home appliances. The mobile application broadly uses in all ages group which plays big roles in managing or doing task in their daily life. By implementing several features in mobile application, they can easily using it at anywhere and anytime. Electrical company have to analyse to use precise technologies in producing security camera which are efficient and meet user requirements. People are demanding strict privacy control devices at their home to prevent criminal acts from occur. User can easily change or control their CCTV camera’s position using feature provided in mobile application. The thickness of camera’s lens is . suitable material in order to customize in outdoor or indoor area and save the image sensor from ruined by sunlight exposure in long term effect. Within flexible and easy to install Wireless CCTV, it is allow user to angle the cameras in their preferred direction instead only in permanent place. Window or door motion sensor that connected with security camera can send alerts and detects the intruder through notification via mobile application.